Diagnostic Accuracy of a Direct Panfungal Polymerase Chain Reaction Assay Performed on Stained Cytology Slides. Issue 3 (May 2021) - Myers, Alexandra N.; Jeffery, Unity; Seyler, Zachary G.; Lawhon, Sara D.; Hoffmann, Aline Rodrigues
Molecular techniques are increasingly being applied to stained cytology slides for the diagnosis of neoplastic and infectious diseases. Such techniques for the identification of fungi from stained cytology slides have not yet been evaluated. This study aimed to assess the diagnostic accuracy of direct (without nucleic acid isolation) panfungal polymerase chain reaction (PCR) followed by sequencing for identification of fungi and oomycetes on stained cytology slides from dogs, cats, horses, and other species. Thirty-six cases were identified with cytologically identifiable fungi/oomycetes and concurrent identification via fungal culture or immunoassay. Twenty-nine controls were identified with no cytologically or histologically visible organisms and a concurrent negative fungal culture. Direct PCR targeting the internal transcribed spacer region followed by sequencing was performed on one cytology slide from each case and control, and the sensitivity and specificity of the assay were calculated. The sensitivity of the panfungal PCR assay performed on stained cytology slides was 67% overall, 73% excluding cases with oomycetes, and 86% when considering only slides with abundant fungi. The specificity was 62%, which was attributed to amplification of fungal DNA from control slides with no visible fungus and negative culture results. Direct panfungal PCR is capable of providing genus- or species-level identification of fungi from stained cytology slides. Given the potential of panfungal PCR to amplify contaminant fungal DNA, this assay should be performed on slides with visible fungi and interpreted in conjunction with morphologic assessment by a clinical pathologist.